(untitled) (Gestão & Regionalidade, 2020)
The objective of this study is to map the theme ’University and regional development’. The instrument used to carry out the research was the Knowledge Development Process Constructivist (Proknow-C) in order to support this research in qualitative and quantitative analysis of articles with scientific recognition and relevant to the proposed theme. Thus, a set of articles was sought through a structured process, in international databases, in which the use of bibliometric analysis techniques was applied to show publications on the subject. From this study, the following results were identified: (i) elaboration of a bibliographic portfolio composed of 19 international scientific articles aligned with the theme; (ii) bibliometric analysis allowed the identification of the main authors, articles, journals and main keywords related to the subject.